A new species of Tityus (Scorpiones, Buthidae) from El Edén Cave, Colombia - Botero-Trujillo, Ricardo; Flórez D., Eduardo (Zootaxa, 2014)
A new scorpion species, Tityus (Tityus) grottoedensis sp. nov., is herein described based on male and female specimens collected in El Edén Cave and its vicinities (Tolima department, Colombia). The new species, which becomes the first scorpion described from a Colombian cave, is probably a eutroglophile or subtroglophile element; however, additional studies are needed to determine the degree of association of the species to the cave. Among other features, the new species is characterized by having a relatively thin body, a yellow-to-chestnut coloration, sternites IV to VI with visible lateral longitudinal carinae, and the basal piece of the middle lamella of the pectines dilated in male and female.